STEAM: Event-based middleware for wireless ad hoc networks. - MEIER, RENE; CAHILL, VINNY (IEEE, 2002)
With the widespread deployment and use of wireless data communications in the mobile computing domain the need for middleware that interconnects the components that comprise a mobile application in distributed and potentially heterogeneous environments arises. Middleware utilizing an event-based communication model is well suited to address the requirements of the mobile computing domain, as it requires a less tightly coupled communication relationship between application components compared to the traditional client/server communication model. This is particularly useful with the use of wireless technology, where communication relationships amongst application components are established very dynamically during the lifetime of the components. Recent research in the area of eventbased middleware for the mobile computing domain focuses on infrastructure network models for wireless data communication. In this paper, we present STEAM, an event-based middleware service that has been specifically designed for wireless local area networks utilizing the ad hoc network model. We argue that an implicit event model is best suited for the envisaged ad hoc environment and present our approach of exploiting a novel combination of three different types of event filter to address the problems related to the dynamic reconfiguration of the network topology as well as their impact on the scalability of a system and the timely delivery of events.
22nd International Conference on Distributed Computing Systems Workshops, 2002. Proceedings.
International Workshop on Distributed Event-Based Systems (DEBS '02),
PUBLISHED
Keywords: Computer Science